Confrontation to Humiliation Complex Causing the Violence, Crime, Uncivilized, Non-Citizenship and Extremism by Positive Education and Cognitions - Kubitary, Amani; Ahmad Alsaleh, Muaweah (International Journal of Criminology and Sociology, 2017)
The individual is the initial unit of society. So, building positive society begins within positive characters of its individuals. The education of the individual must be from a childhood in a positive way, and learn to define goals clearly (presence of clear life goals) and know the meaning in life (Presence and Search for Meaning in Life) and the creation of a purpose in life. This develops a positive, conscious and social personality in the individual who forms society and the world. The absence of positivity, purpose in life and/or meaning in life in individual plays a role in the creation of sadism, negative-sadomasochism personality disorder, barbarism, crime, brutality and extremism among Man who seeks behind the creation of war and destruction and savoring the pains of girls, young people, women and children as Syrian War. Man is not extremist, oblique and criminal by the innate. But, family, parents and their psychological aspect, friends, schools, universities, environmental and media make this oblique and criminal Man. In addition, education of the Civilized Man in life is made to develop his Negative Thought instead of develop his Positive Thought. The result is quite catastrophic. People are most of the time unable to live intensely a happy moment so much they are inhibited from all that is positive. So, Man becomes oblique and criminal by his environment. Crime, uncivilized and extremism have an impact on local communities all over the world. Environmental and their risk factors such as economic difficulties, no activity and no job, negative emotions (disillusioned, resentment, emptiness, boredom, loneliness, or feeling lost and abandoned, no clear purpose in life and no life’s meaning, etc.), absence of coping skills to withstand life stressors, psychological and cognitive development, and ability to make prudent decisions lead acceptance of violent extremist ideologies as crime, uncivilized, violence and extremism. Good citizenship, crime, uncivilized, extremism and violence extremism are the important social issues that might be affected by patterns of thinking (positive or negative) in individuals, institutions, and communities. Positive thinking is as a way for developing good citizenship behavior and confronts the crime, uncivilized, abuse and extremism. Positive thinking about oneself would lead to positive thinking about society; hence develop the link between individuals and their environmental and society by using the positive thinking. So, the RPPT (Repetitions Phrases of Positive Thoughts) can be an effective tool for promoting positive thinking and so building positive identity and positive expectation. Therefore, practicing RPPT, as an educational tool for positive thinking, reinforces positive thoughts which lead the citizenship for better future and a better community. TRPPT (Treatment of Repeating Phrases of Positive Thoughts) contributes in building personal resilience and positive sense of identity that are essential components to prevent violent extremism.